International tourists’ acceptance of Malaysian heritage food choices / Noraini Rahim... [et al.] - Rahim, Noraini (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Malaysia is not only known as a multi-cultural country, but it is also known for its specialized heritage where tourists can find varied food from different cultures in Malaysia. Given that Malaysia is home to several ethnic groups stemming from roots in the colonial period in which hundreds and thousands of immigrants who migrated to what was Malaya before, in search of an honest living in a prosperous country. Food heritage is a term that encompasses the origin of plants and animals, and their dispersal at sites where people first cultivated domesticated plants and animals, and the first places where people first treated, prepared, sold and ate that food. This study was conducted to investigate the acceptance of international tourists towards Malaysian heritage food choices from the different ethnicities of Malay, Chinese and Indian, who represent the largest ethnic groups in Malaysia. Comparing these results is useful because it can provide an initial picture of tourist acceptance. The results of the study may be used to promote the choices of heritage food as an addition to other tourism products as a catalyst to generate business and stimulate the local economy.